2019
DOI: 10.1186/s12885-019-6406-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of forkhead box protein O1 (FOXO1) and paired box 3 (PAX3) in epithelial ovarian cancer

Abstract: BackgroundTranscription factors forkhead box protein O1 (FOXO1) and paired box 3 (PAX3) have been reported to play important roles in various cancers. However, their role in epithelial ovarian cancer (EOC) has not been elucidated yet. Therefore, we evaluated the expression and clinical significance of FOXO1 and PAX3 in EOC.MethodsImmunohistochemical analyses of FOXO1 and PAX3 in 212 EOCs, 57 borderline ovarian tumors, 153 benign epithelial ovarian tumors, and 79 nonadjacent normal epithelial tissues were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
(31 reference statements)
2
19
0
Order By: Relevance
“…Recently, forkhead box-O1 (FOXO1), one of the FOXO subtypes, has attracted attention as an antiobesity target molecule due to its diverse effects in cell cycle control and adipocyte differentiation [ 7 ]. Based on previous studies, FOXO1 was shown to be a tumor suppressor that regulates cell cycles in a variety of human cancers [ 8 , 9 ]. FOXO1 also regulates the cell cycle during adipocyte differentiation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, forkhead box-O1 (FOXO1), one of the FOXO subtypes, has attracted attention as an antiobesity target molecule due to its diverse effects in cell cycle control and adipocyte differentiation [ 7 ]. Based on previous studies, FOXO1 was shown to be a tumor suppressor that regulates cell cycles in a variety of human cancers [ 8 , 9 ]. FOXO1 also regulates the cell cycle during adipocyte differentiation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, FOXO1 expression in cervical cancer tissues was downregulated, and in epithelial ovarian cancer (EOC) tissues was significantly highly expressed. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is characterized by a heterogeneous histopathology with the manifestation of dissimilar genetic and pathway alterations. Major pathways that are aberrantly altered in a range of subtypes include TP53 ( 68 , 69 ), PI3K/AKT ( 70 72 ), VEGF ( 73 , 74 ), EGFR ( 75 , 76 ) and FoxO signaling ( 77 ). It was significant that KEGG and Reactome pathway analyses of the DEGs upregulated in GNA12 -silenced cells directly linked GNA12 to these multiple tumor-promoting pathways.…”
Section: Discussionmentioning
confidence: 99%